Relationship between viral load and pregnancy outcomes among hepatitis B carriers - Ka Wang Cheung; Weilan Wang; Po Lam So; Daniel Wong; Annisa Shui Lam Mak; Winnie Hui; Mimi Tin Yan Seto (Elsevier, 2022)
Objective: Pregnant hepatitis B carriers may have a higher risk of adverse pregnancy outcomes. Current evidences are conflicting regarding the relationship between hepatitis B virus (HBV) and various pregnancy complications, owing to the inclusion of women with different viral activity. This study is to evaluate the relationship between hepatitis B e antigen (HBeAg) status/HBV DNA level and pregnancy outcomes among pregnant hepatitis B carriers in Hong Kong. Materials and methods: This was a retrospective analysis of a prospective multicenter observational study carried out in Hong Kong between 2014 and 2016. Pregnant HBV carriers were recruited. HBeAg was tested. HBV DNA level was quantified at 28-30 weeks of gestation. The rates of gestational diabetes mellitus (GDM), gestational hypertension, pre-eclampsia, preterm prelabour rupture of membranes (PPROM), preterm birth, low birth weight (LBW), macrosomia and mode of delivery were recorded. Results: 679 pregnancies were analyzed. 23.3% of women were seropositive for HBeAg. The mean viral load (SD) at 28-30 weeks of gestation was 3.6 (2.5) log10IU/ml. No statistically significant differences were found in the rates of GDM, gestational hypertension, pre-eclampsia, PPROM, preterm birth, LBW, macrosomia and mode of delivery among women with different viral load levels (≤2 log10IU/ml, 2.01-6 log10IU/ml and >6 log10IU/ml). Positive maternal HBeAg status was not associated with pregnancy complications compared to seronegative women. Conclusion: Seropositive HBeAg status or a higher level of HBV DNA during pregnancy did not pose a significant negative impact to the pregnancy outcomes.